Pengaruh Modal Usaha, Lokasi Usaha, Lokasi Pemasaran dan Kualitas Produk terhadap Pendapatan UMKM - Andrean Syahputra; Ervina Ervina; Melisa Melisa (IPM2KPE, 2022)
This study aims to determine the effect of working capital, business location, marketing location and product quality on MSME income, with loan capital as a moderating variable. This research method is quantitative. This observation was carried out in the Deli Serdang sub-district and used primary data, by conducting a survey using a questionnaire. The data will be tested by, Moderated Regression Analysis (MRA), Absolute Difference Test, Residual Test. The results showed, a) the t value of Business Capital Count -0.066 < 1.976 with a Significant of 0.505> 0.05; b) t value Calculate Business Location 3,564 > 1,976 and sig value = 0.000 < 0.05; c) the value of t Counting Marketing Locations is 2,684 > 1,976 and the value for the significance value is 0,008 > 0,05; d) the value of t Count Product Quality is 0.870 <1.976 while the Amount is at Sig 0.3860 > 0.05; e) The results of the simultaneous test of all variables obtained a calculated F value of 7.866 > F table 2.43 and also a Sig number of 0.000 <0.05. Conclusions, a) business capital does not affect the income of micro, small and medium enterprises and loan capital is not a moderating variable; b) business location affects the income of MSME loans not as a moderating variable; c) marketing location affects the income of micro, small and medium enterprises and loan capital is not a moderating variable; d) product quality does not affect the income of micro, small and medium enterprises and loan capital is not a moderating variable; e) Business Capital, Business Location, Marketing Location and Product Quality Simultaneously influence MSME income. Keywords: Product Quality, Marketing Location, Business Location, Loan Capital, Business Capital, Micro Small Medium Enterprise Income